USE OF AT-SATELLITE TEMPERATURE FOR GEOTHERMAL INVESTIGATION IN IKOGOSI - Bello, Y. A.; Lawal, K. M.; Dewu, B. B. M.; Ikpokonte, A. E. (FUDMA Journal of Sciences, 2020)
Computation of At-satellite temperature provides an opportunity for the detection of shallow thermal anomaly for geothermal exploration. At-satellite temperature is a necessary component for the computation of brightness temperature. The brightness temperature is derived from the inverse of Planck Function. Ikogosi is one of the places in Nigeria with geothermal potential but brightness temperature has not been computed in that region to assess temperature distribution for geothermal exploration. The result of the computed brightness temperature for the thermal band indicates that temperature decreases along SW direction of the study area and it is concordance with the average ground surface temperature. It was also observed that regions around Ikogosi is of temperature above 290 K while that of the vicinity is about 200 K and it could be due to the stream in the vicinity
Keywords: Landsat8, Brightness temperature, Ikogosi and Geothermal